A Comparative Analysis on the Effects of Board Characteristics and Boardroom Gender Diversity on Corporate Performance - Egglestone, Joshua Craig (2016)
This piece addresses the ongoing issue of gender diversity in business, focusing on the area of gender diversity at the board room level of FTSE 100 companies in the United Kingdom. Questioning whether there is value to justify the increasing calls to place more women on company boards. The aim of this study was to measure specific board characteristics and corporate governance factors including, number of women on the board, CEO base pay, number of board meetings etc to establish their effect upon the overall performance of the company as measured by its Tobin’s Q value. Using regression models to identify which board characteristics factors were significantly linked to firm performance. The study found that although there was a low degree of multicollinearity between some of the board characteristics for the data in both 2010 and 2014, these were within a reasonable range. The 2010 data found positive coefficients for factors such as number of executive directors and number of female directors. There were negative coefficients for characteristics such as number of directors and number of meetings. The 2014 data show positive coefficients for both number of female directors and number of female executive directors. While there were negative results for number of directors and number of meetings. These results show that there is evidence to suggest that boardroom characteristics have some affect upon firm performance. In addition to this the women specific board characteristics for both years showed that the introduction of women in the board room also has effects on performance.